2021
DOI: 10.25182/jgp.2021.16.2.119-128
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Cord Blood Saturated Fatty Acid Level and Infant Adiposity

Abstract: This study aimed to assess SFAs profiles in the maternal and cord blood, and the relationship of both SFAs levels with infant adiposity. As many as 99 mothers with singleton pregnancy and pre-pregnancy BMI ≥18.5 agreed to join the research and completed the data collection process. Maternal and cord blood erythrocyte SFAs profile was analyzed using Gas Chromatography-Flame Ionized Detector. Infant birth weight was measured at birth, while infant skinfolds were at 5-7 days postpartum. We used Aris et al. (2013)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Another study found that an increase in total saturated fatty acids, palmitic acid, stearic acid, and behenic acid in cord blood was associated with lower infant adiposity. In contrast, increased levels of maternal caproic acid, capric acid, and lauric acid are associated with higher infant adiposity (Yustiyani et al, 2021). Yammine et al (2018) reported that palmitoleic acid and palmitic acid, as biomarkers of endogenous lipogenesis, were positively correlated with body mass index, especially in women.…”
Section: Relationship Between Palmitic Acid Intake and Palmitic Acid ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Another study found that an increase in total saturated fatty acids, palmitic acid, stearic acid, and behenic acid in cord blood was associated with lower infant adiposity. In contrast, increased levels of maternal caproic acid, capric acid, and lauric acid are associated with higher infant adiposity (Yustiyani et al, 2021). Yammine et al (2018) reported that palmitoleic acid and palmitic acid, as biomarkers of endogenous lipogenesis, were positively correlated with body mass index, especially in women.…”
Section: Relationship Between Palmitic Acid Intake and Palmitic Acid ...mentioning
confidence: 99%
“…Therefore, nutritional interventions during pregnancy have the potential to reduce neonatal adiposity without causing undesirable effects on the neonatal body size or muscle mass. Yustiyani et al (2021) showed that there is a correlation between saturated fatty acid 136 Maternal palmitic acid intake, palmitic acid levels … Aronasty et al levels in cord blood and infant adiposity. The lauric acid level in the cord blood was positively correlated with the triceps skinfold.…”
Section: Relationship Between Palmitic Acid Intake and Palmitic Acid ...mentioning
confidence: 99%
See 2 more Smart Citations